Perspectivas das políticas de habitação de interesse social entre 1988 e 2002: a dinâmica da política municipal na cidade de Vitória - Duarte, Maurizete Pimentel Loureiro (2016)
The present study analyzes the issue of social housing in Brazil, aiming to identify political actions taken by the government in dealing with the housing problems after the release of Carta Maior, between the years of 1988-2002, a period that outlines the timeframe of our study, once it represents a phase of gaps and new alternatives for the social issue of popular housing after the end of the 1980’s. Thus, in the context of the political crisis that surrounds the social housing issue post the extinction of Banco Nacional de Habitação (BNH), we developed our object of study by focusing mainly on a historical analysis of the political and social scenario involving the Política Nacional de Habitação (National Housing Policy) and its perspectives during the mentioned period. We found the dynamics of this policy in some Brazilian municipalities, choosing as research sample the interventions carried out in the city of Vitoria – ES, in the principles of the new guidelines of housing policies implemented in the country. In Vitoria, the socio-environmental approach that the public policies take represents a new understanding of how to address the issue of use and occupation of the urban areas. The most expressive actions are Projeto São Pedro and Projeto Terra, which show the perspectives adopted by urban policies to solve old and permanent housing problems in the lower class. On this study, the methodology is to prioritize the historical-investigative method built on a qualitative approach by making a bibliographical research based on general and specific works on the subject; and on a documentary focus, by making the research on institutional sources, which provided technical and theoretical, conceptual and informative support in the elaboration of this work. Among the results of the actions taken by the housing policy in the time period covered by this work, we point out the new way of dealing with the problems on areas occupied by low-income population, not only in order to minimize the existing risks due to its geomorphological features, that make it unsuitable for residential construction, but mostly considering the basic public assets and services necessary to provide life quality to the families in these areas, in addition to the housing unit that becomes an element to integrate the modalities of drive and solution to housing problems, by not focusing on the traditional model of residential construction in order to reduce housing shortage. We acknowledge that the federal funds intended for the implementation of programs destined to areas inhabited by an increasing number of low-income families are very limited, especially considering the use of these same resources by private sector construction companies.